Roman amphorae from Cioroiu Nou (Romania) - Bondoc, Dorel (Rei Cretariae Romanae Fautorum Acta, 2015)
The archaeological site of Cioroiu Nou, Dolj County, Romania is located in the east-European part of the Roman Empire, in the province of Dacia Inferior. It is probably one of the most important Roman monuments in the south of Dacia. Over the years, there have been a lot of archaeological excavation campaigns: 1938 – led by C. S. Nicolaescu-Plopşor and D. Tudor, 1959 – led by Gh. Popilian, 1960–1961 – by D. Tudor, I. Diaconescu and from 2000 they have been led by the author. It is worth mentioning here some of the most important Roman edifices revealed in the area of the locality: a fortification, a temple, a bath and some other buildings, all these together with a rich archaeological, epigraphic and sculptural material. The inscription of Germanus, speculator of legio VII Claudia and in addition, a significant number of stamped bricks with the name of this military unit, certify the presence of one of its detachments inside a statio, at least in the first half of the 3rd century.